2017
DOI: 10.1002/2017jd027233
|View full text |Cite
|
Sign up to set email alerts
|

Raindrop Size Distribution Measurements at 4,500 m on the Tibetan Plateau During TIPEX‐III

Abstract: As part of the third Tibetan Plateau Atmospheric Scientific Experiment field campaign, raindrop size distribution (DSD) measurements were taken with a laser optical disdrometer in Naqu, China, at 4,508 m above sea level (asl) during the summer months of 2013, 2014, and 2015. The characteristics of DSDs for five different rain rates, for two rain types (convective and stratiform), and for daytime and nighttime rains were studied. The shapes of the averaged DSDs were similar for different rain rates, and the wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
126
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(138 citation statements)
references
References 61 publications
11
126
1
Order By: Relevance
“…Thus, the rain rate R can be estimated eventually with the derived DSD. Similar types of results were reported by Chen and Hu () for the precipitation over the Tibetan Plateau (TP) and the results are also presented in Table . Compared with TP, the second‐degree coefficient of log 10 ( N w )‐ D m for western Pacific is smaller, which might be due to the precipitation over western Pacific containing more large‐size drops than that of TP.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Thus, the rain rate R can be estimated eventually with the derived DSD. Similar types of results were reported by Chen and Hu () for the precipitation over the Tibetan Plateau (TP) and the results are also presented in Table . Compared with TP, the second‐degree coefficient of log 10 ( N w )‐ D m for western Pacific is smaller, which might be due to the precipitation over western Pacific containing more large‐size drops than that of TP.…”
Section: Resultssupporting
confidence: 87%
“… Note . The red marked parts indicate TP values reported by Chen and Hu () for comparison. SWP = south western Pacific; WWP = west western Pacific; NWP = north western Pacific; TP = Tibetan Plateau.…”
Section: Resultsmentioning
confidence: 99%
“…As revealed in previous studies (e.g., Chen et al, ; Tokay et al, ), APUs tend to severely underestimate the number of small particles especially for heavy precipitation. With the focus of accurate retrieval on CR rain rate, instead of using the multimoment fit of DSD, this study proposes an alternative approach of only utilizing the APU measured rain rate as a constraint to evaluate the zeroth moment fit of the DSD.…”
Section: Resultsmentioning
confidence: 54%
“…Studies indicated that the PARSIVEL disdrometer can produce unreasonable results owing to its inherent limitation [44,61]. The unreasonable data must be removed, and some posterior rainfall quantities need to be recalculated.…”
Section: Parsivel Data Processing and Qcmentioning
confidence: 99%
“…However, MMCR is generally deployed in conjunction with other instruments, such as with a CL and disdrometer, because it suffers from signal attenuation and is incapable of detecting the cloud base height under precipitating conditions. A CL and disdrometer can complement more reliable and sophisticated measurements of cloud base height and raindrop spectra information [43,44]. Whereas, inversely, they cannot provide measurements of hydrometeors of aloft cloud and precipitation.…”
Section: Introductionmentioning
confidence: 99%